Investigation of Borosilicate Glasses with Simulated HLW Components and Determination of Their Chemical Durability - S. M. Shaydullin (Uralʹskij federalʹnyj universitet imeni pervogo Prezidenta Rossii B.N. Elʹcina, 2021)
The paper discusses the current status of the HLW vitrification technology applied at the radiochemical plant of the Mayak PA. Conceptual and technical solutions proposed to develop the technology of vitrification of various types of liquid HLW at the Mayak PA are presented. Compositions of borosilicate glasses with HLW components are described, temperatures of their melting and easy pouring are determined. Chemical durability parameters obtained for the borosilicate glasses are provided.